Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sámi Art and Aesthetics: Contemporary Perspectives - Aamold, Svein (Aarhus University Press, 2017)
During the last five decades we have witnessed an increase in activity among artists identifying themselves as Sami, the only recognised indigenous people of Scandinavia. At the same time, art and duodji (traditional Sami art and craft) have been organized and institutionalized, not least by the Sami artists themselves.
OCLC: 1000570833
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Sámi Art Museum: There Is No - Or Is There? - Hanna Horsberg Hansen (Nordlit: Tidsskrift i litteratur og kultur, 2020)
This article aims to answer two questions. The first is: What is a Sámi art museum? The second question considers whether there is no Sámi art museum, as assumed by the Nordnorsk kunstmuseum (NNKM) as the title of a museum performance and exhibition in 2017. To answer the first question, it is necessary to tell the long story of the Sámi cultural-historical museum in Karasjok, Samiid Vuorká-Dávvirat (SVD). This museum was inaugurated in 1972 as an act of resistance against the increasing assimilation politics towards the Sámi population in the post-war period. The building that was erected became a cultural and political centre, and a living cultural institution that housed the increasing Sámi ethno-political movement and its energy. Furthermore, as I will argue, the activity that took place at the site became a part of Sámi cultural heritage. The museum has also collected art since 1972 - a collection that today comprises 1400 artworks. Since the 1980s, various plans have been made for a Sámi art museum in a separate building, somehow connected to SVD, however, none of these plans have yet been realised. The article discusses the different reasons for this, and points to the connotations embedded in the SVD building as a cultural and political centre as one of the contributing factors. To answer the question of whether there is no Sámi art museum, a critical reading of the Nordnorsk kunstmuseum’s 2017 museum performance There Is No is necessary. My answer to the question is that NNKM, unfortunately, fell into several traps in their attempt to focus on the fact that there is no physical building. One such trap, that is very common in Western museums displaying indigenous art, is their use of traditional art-historical models as interpretive lenses when displaying indigenous art. A different concept of what an art museum could be today, as a place where things happen, where we could meet counter narratives, or Sámi art and culture could be presented as being part of the present as well as the past and future, would have been closer to a Sámi art museum. I offer this conclusion both through the deeper understanding of Sámi cultural and ethno-political movements as offered in the story of SVD, and through my reading of the theories of the indigenous American scholar John Paul Rangel. While there may indeed be no physical building claiming to be a Sámi art museum, it does in fact exist through the Sámi concept of árbevierru.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Race-ing Art History: Critical Readings in Reace and Art History - Pinder, Kymberly N (Routledge, 2002)
This comprehensive anthology places issues of racial representation squarely on the canvas. Within these pages are representations of Nubians in ancient art, the great tradition of Westernmasters such as Manet and Picasso and contemporary work by lesser known artists.
OCLC: 804390860
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Decolonizing the Spirit in Education and Beyond: Resistance and Solidarity - Wane, Njoki Nathani; Todorova, Miglena S; Todd, Kimberly L (Palgrave Macmillan, 2021)
This multidisciplinary collection probes ways in which emerging and established scholars perceive and theorize decolonization and resistance in their own fields of work, from education to political and social studies, to psychology, medicine, and beyond
OCLC: 1233305994
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Àbadakone: feu continuel = continuous fire - Dickenson, Rachelle; Hill, Greg A.; Lalonde, Christine (Musée des beaux-arts du Canada, 2020)
Ce survol de l'art contemporain indigène, qui connut un succès retentissant dès son ouverture en novembre 2019, a été prolongé jusqu'au 4 octobre au Musée des beaux-arts du Canada. Àbadakone permet de découvrir des œuvres de plus de 70 artistes qui revendiquent leur appartenance à quelque 40 nations, ethnies et tribus de 16 pays, dont le Canada. Traitant des thèmes de la continuité, de l'activation et de l'interdépendance, Àbadakone explore la créativité, les préoccupations et la vitalité qui marquent l'art indigène de presque tous les continents. L'exposition est organisée par les conservateurs du Musée des beaux-arts du Canada Greg A. Hill, Christine Lalonde et Rachelle Dickenson, conseillés par les commissaires Candice Hopkins, Ariel Smith et Carla Taunton, ainsi que par une équipe d'experts du monde entier. .
Section: 271 pages : illustrations en couleur ; 25 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sakahàn: art indigène international - Hill, Greg A.; Lalonde, Christine.; Hopkins, Candice (Musée des beaux-arts du Canada, 2013)
Sakahàn' celebrates a growing international commitment to the collection, study and exhibition of indigenous art. Featuring more than 75 artists from around the world, this remarkable project places indigenous art squarely at the centre of contemporary art produced today.
Section: 285 p. : ill. en coul. ; 25 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé